Conselho Municipal de Educação de Foz do Iguaçu: histórico e natureza de suas pautas (2012-2017) - Duarte, Adriane Franco (2018)
The present text aimed to analyze the history of formation and the nature of the agenda of meetings of the Municipal Council of Education of Foz do Iguaçu (CME / FI) between the years 2012 to 2017. The theoretical-methodological conception was based on the Dialectical Historical Materialism , supporting the critical analysis of this bibliographic, qualitative and documentary study. The bibliographic research that supported the critical analysis was composed mainly by the following authors: Höfling (2008), Luce and Farenzena (2008), Werle (2008), Lima (2006). In the documentary field, the creation law and its amendment, the Internal Regulation, and the minutes, all these documents of the Municipal Council of Education of Foz do Iguaçu, as well as the notebooks of the National Program for Training Municipal Councilors of Education (Pro-Council), present on the website of the Ministry of Education (MEC). The main considerations were as follows: progress has been made in relation to the minimum conditions for the functioning of the CME / FI, but many struggles will still be indispensable in order to guarantee and implement the necessary conditions to instrumentalize municipal education councils and give them administrative autonomy and financial, which subsidize actions such as the political and technical training of municipal education councilors, and the expansion of technical and financial support.